An ex vivo model of medical device-mediated bacterial skin translocation - Hao Wang (Nature Portfolio, 2021)
Abstract The skin is a barrier and part of the immune system that protects us from harmful bacteria. Because indwelling medical devices break this barrier, they greatly increase the risk of infection by microbial pathogens. To study how these infections can be prevented through improved clinical practices and medical device technology, it is important to have preclinical models that replicate the early stages of microbial contamination, ingress, and colonization leading up to infection. At present, there are no preclinical ex vivo models specifically developed to simulate conditions for indwelling medical devices. Translocation of pathogens from outside the body across broken skin to normally sterile internal compartments is a rate-limiting step in infectious pathogenesis. In this work, we report a sensitive and reproducible ex vivo porcine skin–catheter model to test how long antimicrobial interventions can delay translocation. Skin preparation was first optimized to minimize tissue damage. The presence of skin dramatically decreased bacterial migration time across the polyurethane catheter interface from > 96 h to 12 h. Using visual colony detection, fluorescence, a luminescent in vitro imaging system, and confocal microscopy, the model was used to quantify time-dependent differences in translocation for eluting and non-eluting antimicrobial catheters. The results show the importance of including tissue in preclinical biofilm models and help to explain current gaps between in vitro testing and clinical outcomes for antimicrobial devices.